2022
DOI: 10.1177/19417381221075354
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Exercise Intensity on Psychosocial Outcomes in Musculoskeletal Disorders: A Systematic Review

Abstract: Context: Psychosocial parameters play an important role in the onset and persistence of chronic musculoskeletal disorders (CMSDs). Exercise therapy is a valuable therapeutic modality as part of CMSD rehabilitation. Hereby, exercise intensity is an important factor regarding changes in pain and disability in multiple CMSDs. However, the impact of exercise intensity on psychosocial outcomes remains poorly explored. Objective: To identify the effects of different modes of exercise intensity on psychosocial outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 98 publications
1
2
0
Order By: Relevance
“…The lack of effect of MM is consistent with the findings of Wen et al. [ 31 ] who found that mindfulness interventions, as a PE similar to MM, do not generate an important effect in QOL in LBP patients, but the participants acquired relevant benefits in pain and disability [ 32 ]. A systematic review found that QOL improved with moderate to high intensity exercise interventions.…”
Section: Discussionsupporting
confidence: 87%
“…The lack of effect of MM is consistent with the findings of Wen et al. [ 31 ] who found that mindfulness interventions, as a PE similar to MM, do not generate an important effect in QOL in LBP patients, but the participants acquired relevant benefits in pain and disability [ 32 ]. A systematic review found that QOL improved with moderate to high intensity exercise interventions.…”
Section: Discussionsupporting
confidence: 87%
“…Prior research supports that individuals with nociplastic pain conditions characterized by elevated temporal summation[ 18 ] demonstrate the greatest benefit from low to moderate intensity exercise. [ 43 ] An additional novel finding of this study is that a higher heat pain threshold at a distant site is moderately correlated with greater EIH during low intensity exercise. Heat pain threshold and temporal summation are both C-fiber mediated, suggesting this pathway may be associated with response to low intensity exercise.…”
Section: Discussionmentioning
confidence: 81%
“…First, participants reported demographic factors (age, sex, race, ethnicity) on a standard intake form and completed pain-related psychological questionnaires as these factors can influence response to exercise [30,32]. Participants completed the Pain Catastrophizing Scale (PCS), Fear of Pain Questionnaire-9 (FPQ-9), Pain Anxiety Symptom Scale-20 (PASS-20), and the Brief Resilience Scale (BRS).…”
Section: Methodsmentioning
confidence: 99%